2020
DOI: 10.3389/fped.2019.00558
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Gases for Neuroprotection of Neonates: A Review

Abstract: Importance: Hypoxic-ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. The incidence of HIE is 1-8 per 1,000 live births in developed countries. Whole-body hypothermia reduces the risk of disability or death, but 7 infants needed to be treated to prevent death or major neurodevelopmental disability. Inhalational gases may be promising synergistic agents due to their rapid onset and easy titratability.Objective: To review current data on different inhaled gases with neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Molecular H 2 has become an intensively studied cytoprotective/neuroprotective medical gas in the last decade; for recent reviews of the widespread beneficial effects of H 2 , please refer to [ 39 , 40 , 41 , 42 ]. Concerning HIE, many rodent studies using the Rice–Vannucci model of hypoxic-ischemic stress established the neuroprotective effect of H 2 [ 14 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular H 2 has become an intensively studied cytoprotective/neuroprotective medical gas in the last decade; for recent reviews of the widespread beneficial effects of H 2 , please refer to [ 39 , 40 , 41 , 42 ]. Concerning HIE, many rodent studies using the Rice–Vannucci model of hypoxic-ischemic stress established the neuroprotective effect of H 2 [ 14 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This information would be of great value to clinicians who hope to identify a subpopulation of HIE infants at relatively greater risk for adverse outcomes and who might benefit from additional interventions such as inhaled noble gases or erythropoietin (which demonstrate marginal cost to benefit ratios for general use, but may be of greater value when targeted to a risk-stratified population. 34,35 ) The current gold standard for physiologic-based prediction is the conventional EEG. As described by Murray et al, 13 several different EEG characteristics including background amplitude, the presence of seizures, and the absence of cyclicity were predictive of adverse neurodevelopmental outcome at 2 years of age for infants who underwent hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…This information would be of great value to clinicians who hope to identify a subpopulation of HIE infants at relatively greater risk for adverse outcomes and who might benefit from additional interventions such as inhaled noble gases or erythropoietin (which demonstrate marginal cost to benefit ratios for general use, but may be of greater value when targeted to a risk-stratified population. 34,35 )…”
Section: Discussionmentioning
confidence: 99%
“…Application of therapeutic gases appears to be a straightforward method to achieve neuroprotection as babies born with severe asphyxia usually require assisted ventilation. Medical gas research has identified a number of gases showing neuroprotective effects, including administration of xenon, argon, helium, hydrogen, carbon monoxide, and the management of carbon dioxide and oxygen [8]. The major objective of the present review was to critically examine and discuss the results of the preclinical studies on the neuroprotective effects and the mechanisms of neuroprotection by molecular hydrogen-treatment in HIE animal models, as these were not exhausted in a previous study [8].…”
Section: Introductionmentioning
confidence: 97%
“…Moderate whole body hypothermia offers significant neuroprotection and has been shown to reduce mortality and improve both short-term and long-term neurodevelopmental outcomes [4][5][6]. However, therapeutic hypothermia is unable to save every affected infant, a systematic meta-analysis of 11 cooling trials concluded that the number needed to treat to benefit is 7 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), meaning that on average 7 HIE patients with severe encephalopathy must be cooled to avoid 1 death or major disability [7]. Therefore, adjunct neuroprotective measures are warranted to complement the neuroprotective effect of hypothermia.…”
Section: Introductionmentioning
confidence: 99%